A First Estimate of the Prevalence of Developmental Language Disorder in Mexico: A Retrospective Study - Auza B, Alejandra; Kapantzoglou, Maria; Murata, Chiharu; Méndez-Gómez Humarán, Ignacio (Seminars in Speech and Language, 2024)
This was a retrospective study that aimed to provide a first estimate of the prevalence of developmental language disorder (DLD) in Mexico, where there is currently a lack of epidemiological data on this disorder. Children aged 4;0 to 6;11 years in the cities of Mexico, Queretaro, and Monterrey were classified into two groups: those with DLD (N = 46) and those with typical language development (N = 497). The diagnosis of DLD was based on standardized norm-referenced assessment and language sample analyses. Children with other disabilities were excluded from the final sample. The final sample consisted of 543 children (55% male; 45% female) aged 4;0 to 6;11 years. The estimated prevalence of DLD was 8.5%. The study has clinical implications given that the prevalence of DLD in Mexico may raise awareness of this long-lasting disorder and may help health and educational authorities establish a system to early identify and diagnose children with DLD.
Keywords: developmental language disorder; Spanish-speaking children; monolingual Spanish speakers; prevalence